Deterioration of peripheral microvascular tissue perfusion after transcatheter aortic valve implantation (TAVI) measured by 2D near-infrared spectroscopy (NIRS). (25th November 2020) - Herbrand, T; Baasen, S; Veulemans, V; Kelm, M; Busch, L
Abstract: Background: The data on the effect of transcatheter aortic valve implantation (TAVI) on peripheral microcirculation is scarce. Therefore, in this study, we investigate the changes of peripheral microvascular tissue perfusion before and after TAVI measured by a 2D near-infrared spectroscopy (NIRS) camera. NIRS allows measurement of hemoglobin oxygen saturation (StO2) in the blood perfusing the volume tissue under scrutiny. Methods: In this prospective, single center study, patients with symptomatic, severe aortic stenosis either planned for elective TAVI procedure or elective cardiac catheterization were included. 2-D StO2 maps of all distal extremities (i.e. hand/foot) were acquired before and after TAVI by using a NIRS camera; macrovascular function of the tibial and forearm arteries was assessed by Doppler ultrasound with spectral analysis including ankle-brachial index (ABI) and applanation tonometry. Results: 26 subjects (19 male, age 83±6 years) undergoing TAVI procedure and 5 subjects (4 male, age 76±10) undergoing cardiac catheterization were included in this trial. In the group undergoing TAVI procedure, 5 patients had diabetes mellitus (19%), one of whom was insulin-dependent, 3 patients had a history of peripheral artery disease (12%) and 1 patient had a history of smoking (4%). TAVI procedure was successful without major complications in all cases.Mean peripheral StO2 decreased significantly on all extremities after TAVI, i.e. right hand (from 71±14% to 61±16%; p=0.01), left hand (from 70±12 to 62±16%; p=0.03), right foot (from 70±11% to 61±15%; p<0.01) and left foot (from 66±15% to 58±14%; p=0.03). ABI did not change after TAVI (right ABI baseline mean 1.08±0.2; Δ0.06; left ABI baseline 1.05; Δ0.05). Macrovascular function of the forearm and tibial arteries did not deteriorate as measured by Doppler ultrasound. Furthermore, aortic mean pressure (from 108±21 mmHg to 87±13 mmHg; p=0.002) and augmentation index (from 34±8 mmHg to 24±8 mmHg; p<0.001) decreased significantly while subendocardial viability ratio (from 128±22 to 147±7; p<0.001), a marker for coronary microvascular function, improved significantly after TAVI. In the group undergoing cardiac catheterization, there were no statistically significant changes in macro- or microvascular function. Conclusion: This is, to our knowledge, the first study investigating the effect of peripheral microvascular tissue perfusion measured by NIRS after TAVI. Our results show that peripheral microvascular tissue perfusion was significantly deteriorated after TAVI procedure. Funding Acknowledgement: Type of funding source: None